2002
DOI: 10.4141/p01-088
|View full text |Cite
|
Sign up to set email alerts
|

Leaf development of eight grass species following grazing

Abstract: ), le brome inerme (Bromus inermis Leyss.), la fétuque élevée (Festuca arundinacea (Schreb.) Wimm.) et la phléole (Phleum pratense L.) afin de voir si ces espèces conviennent à la paissance. Les huit espèces ont été soumises à un pâturage de masse par des ovins, à raison de 30 bêtes par hectare. Les auteurs ont ensuite déterminé le stade physiologique des feuilles 7, 14 et 21 jours après la défoliation. Le brome inerme et la phléole donnent toujours le plus grand nombre de feuilles au terme des trois périodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The experimental area for this study was the same as that described by Lardner et al (2002) The 14-ha area was divided into six paddocks, perpendicular to the species strips, using electric fencing and existing perimeter fences. Thus, all species were replicated in all paddocks.…”
Section: Abbreviations: Tnc Total Non-structural Carbohydratesmentioning
confidence: 99%
See 4 more Smart Citations
“…The experimental area for this study was the same as that described by Lardner et al (2002) The 14-ha area was divided into six paddocks, perpendicular to the species strips, using electric fencing and existing perimeter fences. Thus, all species were replicated in all paddocks.…”
Section: Abbreviations: Tnc Total Non-structural Carbohydratesmentioning
confidence: 99%
“…This suggested that timothy exhausted its reserves rapidly, possibly as a result of rapid leaf development rates and successive defoliations from the previous year (Lardner et al 2002) preventing it from storing sufficient carbohydrate reserves for competitive growth the following spring. Colby et al (1974) also reported low reserve levels in timothy after periods of high growth rates.…”
Section: Abbreviations: Tnc Total Non-structural Carbohydratesmentioning
confidence: 99%
See 3 more Smart Citations